Pendekatan Kreatif untuk Meningkatkan Minat Baca Anak di Rumah Baca Rambutan - Aliya Azzahra; Stevhani Carolina Hutauruk; Tasya Manik; Devita Daniati Sinaga (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Reading interest in children is a crucial factor in enhancing literacy skills and knowledge. Rumah Baca Rambutan, as a literacy center, plays a strategic role in fostering a reading culture, particularly among children. This study aims to explore the use of literacy posters as a tool to cultivate children's interest in reading. The method employed is a qualitative approach through observations and interviews with the library's staff and children visitors. The findings reveal that visually appealing and informative literacy posters can effectively motivate children to read more books and explore various new topics. Moreover, literacy posters serve as an educational medium to instill positive values. Through this creative approach, Rumah Baca Rambutan successfully creates an environment that supports the development of a reading culture among children. This study concludes that literacy posters hold significant potential to enhance children’s reading interest in various literacy-focused settings.